El desarrollo de una solución empresarial de punto de ventas - POS para la ventas de los productos de la Empresa Sinetics - Salvador Amaya, Raisa Lisette Estefania (2021)
This report addresses one of the main problems regarding Sales and Collections _x000D_ Planning in the company Soluciones Integrales de Negocios y Tic’s S.R.L. in Peru, which is _x000D_ dedicated to the sale of technological products and consulting on technology solutions. _x000D_ Considering the operational functions that the company performs, as well as other ones _x000D_ of the same business area; the analysis, design and implementation of a Point of Sales _x000D_ business solution was carried out that will be used by the company and then marketed as _x000D_ a technological product developed by the IT Project Development department._x000D_ The sales planning that the company does is based on orders made by its _x000D_ customers, also, under direct sales at a point of sale such as a store. Collection planning is _x000D_ carried out on credit, with a payment schedule that is established in each contract with a _x000D_ client or in a cashing on delivery of the product with different forms of payment such as _x000D_ cash, deposits, check, debit card and credit card._x000D_ The implementation of a Point of Sales as a business solution covers the real _x000D_ problem: the delay and low precision in obtaining daily sales reports that the sales _x000D_ executives do manually, directed to Commercial Management. Then, the main goal was _x000D_ to develop a Point of Sales business solution for commercial management based on the _x000D_ PMBOK and RUP methodology, this solution will reduce time and increase precision in _x000D_ sales planning and collections._x000D_ The results obtained during the use of the business solution were compared with _x000D_ those without the application, which confirmed the objective suggested: the reduction of _x000D_ the time used, and the increase in the precision of its information for decision-making